Transforming Organizational Quality Through Effective Administrative Training - Faiz, Hasanul; Al-Amin, Muhammad Fath; Mundiri, Akmal; Fahmi, Aqil (Communautaire: Journal of Community Service, 2023)
The focus of this study is to analyze the effectiveness of administrative training in improving the organizational quality of Madrasah Aliyah Nurul Jadid Religious Specialization. The purpose of this study was to evaluate the impact of administrative training on improving the organizational spirit, self-mastery, and leadership ability of the participants in the context of Madrasah Aliyah Nurul Jadid Religious Specialization. This research method will use a qualitative approach with data collection techniques in the form of participatory observation and in-depth interviews. Observations will be made to understand existing administrative practices, while interviews will be used to gain a deep understanding of participants' experiences in administrative training. Data analysis was carried out thematically to identify patterns that emerged in the development of the participants' organizational spirit, self-mastery, and leadership abilities. The results showed that administrative training succeeded in improving the organizational spirit, self-mastery, and leadership ability of the participants in Madrasah Aliyah Nurul Jadid Religious Specialization. Participants demonstrated improvement in their understanding of effective administrative practices, as well as being able to identify and address emerging challenges in administrative management. In addition, they also showed improvement in the ability to work in teams, manage themselves, and lead effectively in a madrasah context. These findings show that administrative training has a positive impact in improving the quality of madrasah organization and personal development of the participants. The implication of this research is the importance of providing effective administrative training for madrasah staff and leaders to improve the quality of organization and personal development of the participants.